ETOS KERJA KEPALA MADRASAH DALAM MENCAPAI KEBERHASILAN MADRASAH” (STUDY KASUS DI MADRASAH IBTIDAIYYAH DARUL HUFFAZ DESA BERNUNG KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN PROPINSI LAMPUNG) - Mat Rais; Taqwatul Uliyah; Cipto Handoko (Journal of Islamic Education and Learning, 2022)
Madrasah is one of the places to print the young generation of Indonesia. When a madrasa is able to produce quality young people, it can be said that the madrasa is a successful madrasa. The success of a madrasa cannot be separated from the important role of a madrasa head. To make a successful madrasa, it takes a madrasa principal who has a good work ethic so that he is able to achieve the planned goals. When that goal has been achieved, that's where the madrasa is called successful. The purpose of this paper is to analyze the four indicators of the Madrasah Principal's Work Ethic in Achieving School Success at MI Darul Huffaz, Bernung Village, Gedong Tataan District, Pesawaran Regency, Lampung Province, for the 2021/2022 Academic Year. The method used in this study is a qualitative method. The results of this study found that: Hard work, discipline, responsibility and pride in the profession carried out by the madrasa principal in his leadership at the madrasa was very good so that it had a good impact on the progress and success of the madrasah